Evaluation of Residues of Amazonian Fruit Piquia (Caryocar villosum) as Sustainable Ingredient for Sunscreen and Cosmetic Formulations - Izadora de Souza; Gabriella C. P. Grimmelprez; Klenicy K. L. Yamaguchi; Johannes Schleusener; Silke B. Lohan; Martina C. Meinke; Lorena R. Gaspar (Antioxidants, 2025)
Amazonian fruit residues like piquia shells are often discarded despite their antioxidant potential for sustainable cosmetic use. This study evaluated the photostability, phototoxicity, and photoprotection of hydroalcoholic piquia shell extract (PqSE) combined with UV filters in solutions and cosmetic formulations. PqSE formulations were photostable, even stabilizing photounstable UV filters. Phototoxicity tests (OECD TG 432) showed no phototoxic potential (MPE < 0.15) and reduction in the phototoxic potential of UV filters, while ocular irritation potential via HET-CAM assay indicated no irritant effects. The extract combined with UV filters enhanced protection against UVA-induced reactive oxygen species (ROS) production, achieving 60.9% effectiveness, outperforming commercial photostabilizers. Against UVB radiation, it showed cellular viability above 80%, comparable to benzophenone-3. PqSE formulations exhibited a radical protection factor (RPF) nine times higher than controls and reduced radical production by 64% after visible/near-infrared (VIS/NIR) irradiation on porcine skin, compared to 38% for controls. Confocal Raman microspectroscopy showed penetration depths below 12 µm for all time points. This study highlights the potential of reusing fruit residues like PqSE as sustainable, effective ingredients in sunscreen formulations, offering enhanced photoprotection and reduced environmental waste.